Virtual real model of a laser focus control system - Kabar Kyaw (2008)
A virtual model of the laser welding control system is built. The virtual model is expected to capture many essential features of the process that are critical to the controller design and incorporate the process dynamics. This model can also enable user to do system testing, operator training, and controller tuning.